Penggunaan Media Pop Up Book sebagai Media Belajar yang Menyenangkan di Rumah Dalam Inovasi Pembelajaran SD Kelas Rendah - Anisa Nurul Izzah; Deni Setiawan (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
By applying it, learners walk boldly, educators cannot unite and pay attention to their students directly. This makes educators have to rack their brains to increase student interest in learning. The use of printed books as learning media tends to make students bored, thereby reducing students' interest in learning. Popup books are one solution to increase student interest in learning. This happens because the pop up book provides a 3D picture so it is not monotonous. This study uses the library method with the results of collecting information or empirical data through various literatures including books, other references, and relevant previous research results so as to get answers to the problems studied. This method uses editing, organizing, and finding data collection techniques.